A Systematic Approach to Discover and Characterize Natural Plant Biostimulants - Povero, Giovanni; Mejia, Juan F.; Di Tommaso, Donata; Piaggesi, Alberto; Warrior, Prem (Frontiers in Plant Science, 2016)
The use of natural plant biostimulants is proposed as an innovative solution to address the challenges to sustainable agriculture, to ensure optimal nutrient uptake, crop yield, quality, and tolerance to abiotic stress. However, the process of selection and characterization of plant biostimulant matrices is complex and involves a series of rigorous evaluations customized to the needs of the plant. Here, we propose a highly differentiated plant biostimulant development and production platform, which involves a combination of technology, processes, and know-how. Chemistry, biology and “omic” concepts are combined/integrated to investigate and understand the specific mode(s) of action of bioactive ingredients. The proposed approach allows to predict and characterize the function of natural compounds as biostimulants. By managing and analyzing massive amounts of complex data, it is therefore possible to discover, evaluate and validate new product candidates, thus expanding the uses of existing products to meet the emerging needs of agriculture.